Antisipasi Degradasi Moral di Era Global - Muthohar, Sofa (Nadwa, 2013)
In the globalization era, environment has a broad definition. Someone could very easily find an atmosphere that he likes. It brings to positive or negative effects. Teenagers (aged 12-22 years) are the generation most vulnerable to the negative influences that lead to moral decadence. This problem is very difficult to overcome if it just rely on the secular West psychological the-ories. Islamic education is expected to provide a solution to these problems through functional strategy, integral and progressive. Religious teachings not only memorized but should also be presented in the spirit to assist young people in solving the problem. This strategy could be: guiding problem solv-ing in dealing with problems themselves and society as well as the formation of an integral understanding of his relationship with God. Teens should have spirit that can transform itself into a superior person.